Idiom Translation Quality Assessment on “Landline” Novel by Rainbow Rowell - Richard Ferry Nugraha (General English Education, 2023)
This study aimed at assessing the quality of idiom translation in a novel entitled “Landline” by Rainbow Rowell. By referring to Nababan’s Translation Quality Assessment model (2012), this study assessed the idioms’ translation according to the degree of accuracy, acceptability, and readability. The data analyzed in this study include the idioms and Indonesian translations, as well as the assessment result made by three expert assessors. Those idioms were identified and grouped based on the classification adapted from Palmer (1981). There are 37 idioms found, which consist of 2 idioms that can undergo syntactic changes, 10 idioms with syntactic limitation, 10 frozen idioms, 5 partial idioms, and 10 phrasal verbs. The findings show that the Indonesian translation of those idioms generally has a high-quality level, especially those which were translated into equivalent idioms in the target language. Paraphrasing also plays a major role as a translation strategy used by the translator. However, this strategy may sometimes lead to distortion of the original message in the target language.